2019
DOI: 10.1155/2019/7853492
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA Containing (dG)n Motifs Penetrates into MCF7 Breast Cancer Cells, Induces the Adaptive Response, and Can Be Expressed

Abstract: Background Oxidized human DNA or plasmid DNAs containing human ribosomal genes can easily penetrate into the breast cancer cells MCF7 and stimulate the adaptive response induction. Plasmid DNA containing a CMV promoter, gene EGFP, and the insertion of the human ribosomal genes can be expressed. A hypothesis is proposed: these features of the ribosomal DNA are due to the presence of dGn motifs that are prone to oxidize. Methods Cells of MCF7 line were cultured with plasmids which contained a CMV promoter and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…The activation of the sensors launched synthesis of pro-inflammatory cytokines. By the example of model DNA fragments, which contained various numbers of GC-rich and oxidized motifs, it was previously shown that cfDNA could be a potential trigger of adaptive response in the cells and serve as an active agent in the realization of the bystander effect upon the exposure to ionizing radiation [ 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 56 , 57 , 58 ]. In this paper, we studied for the first time the ability of real cfDNA samples from human plasma to induce the adaptive response in the cells via the mechanism, which had been earlier described for model DNA fragments only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the sensors launched synthesis of pro-inflammatory cytokines. By the example of model DNA fragments, which contained various numbers of GC-rich and oxidized motifs, it was previously shown that cfDNA could be a potential trigger of adaptive response in the cells and serve as an active agent in the realization of the bystander effect upon the exposure to ionizing radiation [ 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 56 , 57 , 58 ]. In this paper, we studied for the first time the ability of real cfDNA samples from human plasma to induce the adaptive response in the cells via the mechanism, which had been earlier described for model DNA fragments only.…”
Section: Discussionmentioning
confidence: 99%
“…It was found earlier that model samples of oxidized DNA (oxy-gDNA), in contrast to non-oxidized gDNA, induced an adaptive response in human cells, which is similar to the cells’ response to small doses of ionization radiation [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The response includes the transient induction of reactive oxygen species (ROS) synthesis by NOX4 (NADPH-oxidase 4) pro-oxidant enzyme.…”
Section: Introductionmentioning
confidence: 97%
“…RIG-I functions as a cytosolic receptor detecting exogenous RNAs. RIG-I is able to detect 5′-triphosphorylated dsRNA transcribed from AT-rich dsDNA by DNA-dependent RNA polymerase III (Pol III) [ 42 , 59 , 60 , 61 ]. Apparently, cfDNA penetrating into the cell is transcribed with the formation of dsRNA molecules that interact with RIG-I.…”
Section: Introductionmentioning
confidence: 99%
“…Ранее мы показали, что окислительная модификация внеклеточной ДНК при добавлении в среду культивирования раковых клеток линии MCF7 способствует ее проникновению в цитоплазму клеток [3]. Облучение рентгеновским излучением в дозе 10 сГр раковых клеток MCF7 после добавления ГЦ-обогащённых плазмид в среду их культивирования приводило к повышению уровня 8-oxodG в плазмидах через 30 минут после облучения и к более интенсивному проникновению окисленных плазмид по сравнению с аналогичным экспериментом без облучения [4].…”
Section: Introductionunclassified